Intrigues du pouvoir dans Les amours tragiques de Pyrame et Thisbé de Théophile de Viau - Zsák, Helga (Verbum – Analecta Neolatina, 2011)
Théophile de Viau, a very talented poet of the early 18th century, wrote his Tragic Love of Pyrame and Thisbé in 1621, and this work was one of the most successful plays of the whole century. Inspired by Ovid, the play shows many similarities with Shakespeare’s Romeo and Juliet, but seems to depict the presence of authority and despotism more sharply. In this context, the contrast between the treatment of the themes of power, generosity, liberty and care, is deep, lyrical and moving.